An assessment of governance of marine and coastal resources on Koh Tao, Thailand. (1st November 2017) - Satumanatpan, Suvaluck; Moore, Patti; Lentisco, Angela; Kirkman, Hugh
Abstract: This was the first assessment of marine and coastal resource governance on Koh Tao, a small island in the Western Gulf of Thailand. The study assessed perceptions of governance of marine and coastal resources among national and provincial authorities and Koh Tao residents on the basis of governance components − law, institutions and process − and governance principles − transparency, participation, rule of law, accountability and access to justice. Governance to deal with the anticipated continued growth in marine-based tourism is challenged. The study identified misunderstandings about governance and governance weaknesses, which, if they are not addressed, will be obstacles to the future sustainable development of Koh Tao. The research findings indicate that supporting local governance will be key to maintaining sustainable use of marine and coastal resources on the island and ensuring the sustainability of the local economy, which depends on these resources. We suggest a number of recommendations that can apply generally in countries wishing to conserve marine and coastal biodiversity and use those resources sustainably on coasts and islands. Highlights: Inaction by government authorities - local governance process fills gap. Improve local institutions' capacity for coordination. Improve local capacity to facilitate public participation and communication. Build public awareness of economic value of marine and coastal resources.